2003
DOI: 10.1136/emj.20.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Review of prehospital sodium bicarbonate use for cyclic antidepressant overdose

Abstract: Objective: To describe the clinical presentation of patients with cyclic antidepressant (CA) and use of sodium bicarbonate (NaHCO 3 ) in the treatment of this overdose in the prehospital setting. Methods: A three year retrospective observational review of records was performed using the San Diego County Quality Assurance Network database for prehospital providers. All adult patients who were treated with NaHCO 3 by paramedics for a CA overdose were included. Demographic data, presenting cardiovascular and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
5
1
1
Order By: Relevance
“…10 Calkins et al ., reported that a GCS score of 8 and under was 47% in TCA poisonings. 22 According to our study, mean GCS score was found to be 14 on first evaluation of the patients. Additionally, the majority of patients with a GCS score of 8 and under were poisoned by TCAs and those patients were intubated at a higher rate than patients with a GCS score of 9 and over.…”
Section: Discussionmentioning
confidence: 60%
“…10 Calkins et al ., reported that a GCS score of 8 and under was 47% in TCA poisonings. 22 According to our study, mean GCS score was found to be 14 on first evaluation of the patients. Additionally, the majority of patients with a GCS score of 8 and under were poisoned by TCAs and those patients were intubated at a higher rate than patients with a GCS score of 9 and over.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, low GCS on admission was identified as an independent risk factor for the development of life-threatening complications such as seizure and a predictor of bad prognosis after amitriptyline poisoning (Paksu et al, 2014). Furthermore, the increased incidence of seizure reported together with low GCS was found in a study of TCAs overdose by Calkins et al (2003).…”
Section: Discussionmentioning
confidence: 90%
“…4 TSA zehirlenmesi olan hastaları konu alan iki çalışmada hipotansiyon oranları %33 ve 34 bulunmuştur. 7,8 Bizim çalışmamızda hipotansiyon birinci grupta 1 (% 3,3), ikinci gruptaysa 2 (%7,1) hastada görüldü. Hipotansiyonla gelen hastalarda NaHCO 3 tedavisiyle birlikte sıvı tedavisi yeterli oldu ve tedavide TSA zehirlenmelerinde EKG anormalliği gö-rülme oranının %37 olduğu bildirilmiştir.…”
Section: Discussionunclassified